The validation of the Indonesian version of psychotic symptoms ratings scale (PSYRATS), the Indonesian version of cognitive bias questionnaire for psychosis (CBQP) and metacognitive ability questionnaire (MAQ) - Erawati, Erna; Keliat, Budi; Daulima, Novy (International Journal of Advanced Nursing Studies, 2014)
Aim: The present study was to validate the Indonesian version of Psychotic Symptoms Ratings Scales (PSYRATS), the Cognitive Bias Questionnaire for Psychosis (CBQp) and the Metacognitive Ability Questionnaire (MAQ) as a new scale to measure the ability of metacognition of schizophrenia. Background: The PSYRATS, CBQp, and MAQ have demonstrated their usefulness for the assessment of hallucinations and delusions, cognitive biases and metacognitive ability in schizophrenia. So far no validation of the Indonesian version has been carried out. Methods: The PSYRATS, CBQp and MAQ were administered to 155 subjects with a diagnosis of schizophrenia. Factor structure, reliability, test-retest stability, and convergent validity were analyzed. Findings: We found that the all psychometric were reliable and valid. Indonesian version of the PSYRATS and CBQp Indonesian version have high reliability. The reliability of new psychometric of MAQ was Cronbach’s alpha=.759 and was checked in a subsample (n=32; r=.668; p<.01). Conclusions: Similar to the original PSYRATS and CBQp, the Indonesian version of PSYRATS and CBQp have good psychometric properties. The new psychometric of MAQ is a valid instrument for assessing metacognition. Implications for future research are discussed. Keywords: Schizophrenia; Hallucination Severity; Delusion Severity; Bias Cognitive for Psychosis; Metacognition: Instrumental Study.